2022
DOI: 10.1186/s13756-022-01147-2
|View full text |Cite
|
Sign up to set email alerts
|

Detecting inappropriate total duration of antimicrobial therapy using semi-automated surveillance

Abstract: Objectives Evaluation of the appropriateness of the duration of antimicrobial treatment is a cornerstone of antibiotic stewardship programs, but it is time-consuming. Furthermore, it is often restricted to antibiotics prescribed during hospital admission. This study aimed to determine whether mandatory prescription-indication registration at the moment of prescribing antibiotics enables reliable automated assessment of the duration of antibiotic therapy, including post-discharge duration, limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…As some of the validated treatment courses within the validated sample of UTI, RTI, IAI or other infections were also of extended duration or in readmitted patients these were also excluded. The error rate of extracted indications was comparable with the error rates we found in an earlier study [ 9 ]. In 21.0% of courses the extracted indication did not match the indication of the treatment course found in the EHR.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…As some of the validated treatment courses within the validated sample of UTI, RTI, IAI or other infections were also of extended duration or in readmitted patients these were also excluded. The error rate of extracted indications was comparable with the error rates we found in an earlier study [ 9 ]. In 21.0% of courses the extracted indication did not match the indication of the treatment course found in the EHR.…”
Section: Resultssupporting
confidence: 89%
“…When considering only courses with post-discharge treatment, we observed that a similar proportion of treatment courses was given post-discharge. Our previous study showed that many infections are still treated too long and a considerable amount of this excessive treatment is given post-discharge [ 9 ]. Possible stewardship interventions could focus on antibiotic overuse at discharge for both CAI and HAI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations